2015
DOI: 10.3168/jds.2014-8288
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: The gain-of-function Y581S polymorphism of the ABCG2 transporter increases secretion into milk of danofloxacin at the therapeutic dose for mastitis treatment

Abstract: The ATP-binding cassette transporter ABCG2 restricts the exposure of certain drugs and natural compounds in different tissues and organs. Its expression in the mammary gland is induced during lactation and is responsible for the active secretion of many compounds into milk, including antimicrobial agents. This particular function of ABCG2 may affect drug efficacy against mastitis and the potential presence of drug residues in the milk. Previous in vitro and in vivo studies showed increased transport of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 33 publications
(38 reference statements)
3
21
0
1
Order By: Relevance
“…In this study, we examine the relevance of the Y581S polymorphism on the transport of endogenous and dietary compounds present in cow milk as previously reported for milk secretion of fluoroquinolone drugs such as danofloxacin 2015).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, we examine the relevance of the Y581S polymorphism on the transport of endogenous and dietary compounds present in cow milk as previously reported for milk secretion of fluoroquinolone drugs such as danofloxacin 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, milk/plasma ratio was much higher in Y/S cows (2.99 ± 0.46) than in Y/Y cows (1.44 ± 0.50), which corroborated the in vitro results obtained with the S581 variant. The Y581S SNP of the bovine ABCG2 can affect the plasma concentration of several substrates (Otero et al, 2015). We hypothesize that the decrease in plasma disposition of specific substrates of ABCG2 in Y/S cows is probably due to the enhanced function of the Y581S polymorphism.…”
Section: Enterolactonementioning
confidence: 88%
See 2 more Smart Citations
“…The adaptability of rumen microbiota is a key feature of ruminant physiology and survival strategy (Russell and Rychlik, 2001; McCann et al, 2014a; Zanton, 2015). It has been shown that whenever cows undergo a ration change rumen microbiota needs between 1 day and sometimes even longer than 3 weeks to adapt and stabilize, depending on the group of bacteria, archaea, fungi, or protozoa, the extent of diet change and the behavioral adaptation required (Hackmann, 2015). de Menezes et al (2011) have shown in a cross-over design, with 2 weeks for diet adaptation, that the liquid and solid rumen bacterial and archaeal community of TMR and pasture fed dairy cows differs significantly.…”
Section: Introductionmentioning
confidence: 99%